Social Support and Student Engagement Among Deaf or Hard-of-Hearing Students. (November 2021) - Cheng, Sanyin; Deng, Meng; Yang, Yuqin
This study explores how students' social support are related to their engagement, by administering the Chinese Version of Zimet's Multidimensional Scale of Perceived Social Support (MSPSS-C) and the Student Engagement Scale to 225 deaf or hard-of-hearing (D/HH) school students in mainland China. Results show that, among all participants, those with higher levels of social support scored higher on student engagement, whereas those with lower levels of social support had lower scores. The contributions, limitations, and implications of the present research are discussed.